Effect of Dual and Triple Energy Window Scatter Correction Methods on Image Quality in Liver Scintigraphy - Perisinakis, K.; Karkavitsas, N.; Damilakis, J.; Gourtsoyiannis, N. (Nuklearmedizin - NuclearMedicine, 1998)
Aim: To investigate the effect of two scatter correction methods on lesion detectability for both planar and tomographic hepatic imaging. Methods: All planar and tomographic acquisitions involved simultaneous collection of photons in the main photopeak window (126-1 54 keV) and three additional windows (92-116, 116-126 and 154-164 keV). Uncorrected and corrected for scatter images were obtained from the same acquisition data. The dual energy window (DEW) and the triple energy window (TEW) scatter compensation methods were used to obtain two sets of corrected images. The DEW method was implemented with main photopeak window 126-154 keV, Compton scatter window 92-126 keVand scatter multiplier k = 0.5. A modified TEW method was also applied with main photopeak window 126-154 keV and scatter subwindows 116-126 keV and 154-164 keV. Phantoms were used to study the effect of scatter correction on contrast and signal-to-noise ratio. The observer’s ability to identify lesions was studied on uncorrected and corrected for scatter patient images. Results: In planar imaging, both scatter compensation methods yielded contrast enhancement. However signal to noise ratio (SNR) was degraded to 0.63 and 0.67 when DEW and TEW were applied respectively. In SPECT images, contrast was increased by a factor of 2.4 and 1.7, while SNR was degraded to 0.60 and 0.64 when DEW and TEW methods were used respectively. Conclusions: Scatter correction using DEW and TEW methods may improve observer’s ability to distinguish lesions in planar (p<0.05 for both methods) and SPECT (p<0.05 for both methods) liver studies.
Keywords: Scatter correction; scintigraphic imaging; SPECT; liver